2021
DOI: 10.3390/ani11061569
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Single and Triple Testicular Biopsy Using Biopty Gun on Spermatogenesis in Pubertal Rats

Abstract: Background: The aim of this study was to compare consequences in single and triple testicular biopsy by biopty gun in pubertal rats using histological and immunohistochemical analysis. Methods: Thirty-two Sprague-Dawley male rats were used as the experimental model. The rats were randomly divided into three study groups. The rats from the first group (n = 12) received a single-biopsy of upper pole of the left testis, while the rats from the second group (n = 10) received triple-biopsy of upper and lower poles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…After that period, the possibility of spontaneous testicular descent is extremely low. Recent recommendations suggest that optimal timing for orchiopexy, to avoid infertility and testicular cancer is between 6 and 18 months of age [1][2][3][4][5]26]. Although there are many controversies regarding hormonal therapy in boys with non-palpable cryptorchidism, a recent systematic review and meta-analysis showed that hormonal therapy can be effective in some cases and increase the success rate of complete testicular descent [27].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…After that period, the possibility of spontaneous testicular descent is extremely low. Recent recommendations suggest that optimal timing for orchiopexy, to avoid infertility and testicular cancer is between 6 and 18 months of age [1][2][3][4][5]26]. Although there are many controversies regarding hormonal therapy in boys with non-palpable cryptorchidism, a recent systematic review and meta-analysis showed that hormonal therapy can be effective in some cases and increase the success rate of complete testicular descent [27].…”
Section: Discussionmentioning
confidence: 99%
“…The most recent study demonstrated that despite on-time orchiopexy, up to 25% of the children with UDT have an increased risk for infertility [4]. To identify the cases at high risk for infertility and who will require further treatment, blood sampling and testicular biopsy are required [4,5]. In addition to male infertility, as the most important consequence of cryptorchidism, boys with UDT are at a significantly higher risk of developing testicular tumors or testicular torsion, and are also more susceptible to testicular trauma compared to boys with normally positioned testicles [1,[5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation